(untitled) (Research, Society and Development, 2021)
Consumers are more demanding for the quality of products and their health benefits, as well as the search for more practical foods. Sausage foods are presented in a wide variety of categories in a growing market. Goat (or goat) meat, rich in good quality proteins and lipids, has been arousing the interest of consumers and motivating research for the production and development of new meat products. This study aimed to identify, through the scientific literature, the technological advantages of goat meat in the use of meat products and its influence on the physicochemical and sensory characteristics of these foods. This study is a narrative review, whose articles were searched in the scientific databases Science Direct, PubMed, and academic Google, using the following search terms: "sausage" OR "meat products" AND "goat meat". A research article was included, available in full, free, and published between the years 2019 and 2021. The literature showed that goat meat is nutritionally rich and has healthy fats and low calories. In addition, it presented the technological potential for the elaboration of meat products, such as sausages, sausages, nuggets, pates, and hamburgers. As well as acting as a promoter of changes in the nutritional, sensory and physicochemical characteristics of the products. Goat meat can be used as one of the raw materials in the development of meat products with high utilization, added value and technological potential, quality (sensory and nutritional), and safe.